HUBUNGAN ANTARA BODY IMAGE DENGAN PERILAKU DIET PADA REMAJA KELAS XI IPA 3 DAN 4 SMA N 1 POLANHARJO KLATEN - Sri Yulianti, Tunjung; Indriati, Ratna (Intan Husada : Jurnal Ilmiah Keperawatan, 2015)
Introduction: body  image  (body  image)  to  form  one's  perception  of the body,  both internally  and  externally,  this  perception  includes  feelings and attitudes aimed at the body that are affected by personal views about the characteristics and the physical ability and the perception of other people's views.  Many  teens  consider  themselves  overweight  or  obese easily become so frequent diet in a way that is less true as to limit or reduce the frequency  of meals  and  the  number  of  meals,  vomit  frequently eaten, so long there is no appetite is very dangerous for teens.Purpose  of  the  study: was  to  analyze  the  relationship  between body image and dieting behaviors in adolescents Subjects: Population and samples of this study were 60 male and female students  in  class  XI  IPA  3 and  4  in  SMA  Negeri  1  Polanharjo using saturation sampling technique in order to obtain 60 to be the respondent.  Method  : This research  method using cross  sectional  approach, using a questionnaire  with  a scale  measuring interval.  Data  were  analyzed  with Chi-Square. Results: as  many  as  43 respondents  (71.67%)  have  a  positive  body image  and  as  many  as  59 respondents  (98.33%) do  a  good  dietary behavior.  There  is  a  significant relationship  between  body  image and dieting behaviors (p = 0.016).  Conclusion : There  is  a  relationship  between  body  image  and dieting behaviour in adolescents.Keywords: Body image, dieting behaviors, teen